"Ain't I a Bastard, Well I Received My Training in Aussie": The Life of Frank Maybank, an Australian Trade Unionist in Central Africa. (1st May 2022) - Money, Duncan
Abstract : This article examines the working life of Frank Maybank (1901–94), a self-described Australian trade unionist on the Central African Copperbelt. Maybank was in many ways a worker of the world, he lived and worked in several countries and did all manner of jobs. The job he held the longest was General Secretary of the whites-only mineworkers' union on the Copperbelt, where his militancy was closely informed by his experiences in, and contacts with, the Australian labour movement. This article uses Maybank's biography both to show the transnational connections that existed and to argue that the relative weakness of those connections allowed information about different places to be misrepresented. What this article terms "strategic misunderstandings" allowed distant events and movements to be misrepresented to suit domestic audiences and concerns in Australia and on the Copperbelt. In addition, this paper reflects on how the practice of writing transnational history and how the uneven nature of digitised sources may shape the development of this sub-field.